Sonochemical degradation of N-methylpyrrolidone and its influence on single walled carbon nanotube dispersion. Issue 93 (25th September 2015) - Yau, Hin Chun; Bayazit, Mustafa K.; Steinke, Joachim H. G.; Shaffer, Milo S. P.
Abstract : During sonication, NMP degrades to form organic nanoparticles, likely to contaminate SWNT and other nanomaterial dispersions. Abstract : Sonicating pure N -methyl pyrrolidone (NMP) rapidly produces contaminating organic nanoparticles, at increasing concentration with time, as investigated by AFM, as well as UV-vis, IR and NMR spectroscopies. The contamination issue affects carbon nanotube, and likely other nanomaterial, dispersions processed by sonication in organic solvents.